Perceptions of HIV and mental illness as "Western" or "Traditional" illnesses: a cross-sectional study from Limpopo Province, South Africa - Michael Galvin; Lezanie Coetzee; Patricia Leshabana; Nthabiseng Masebe; Shitshembiso Lebepe; Aneesa Moolla; Amanda R. Tarullo; Peter C. Rockers; Denise Evans (BMC, 2024)
Abstract Although Western biomedical treatment has dramatically increased across sub-Saharan African health systems, traditional medicine as a form of healing and beliefs in supernatural powers as explanations for disease remain prevalent. Research in this region has identified HIV in particular as a disease located within both the traditional African and Western medical paradigms, whilst mental illness is ascribed to primarily supernatural causes. Within this context, this study sought to understand and explore the perceptions of HIV and mental illness among a population of rural women in Limpopo, South Africa. 82 in-depth interviews were conducted between January and December, 2022. Interviews were transcribed and translated into English. Data were managed using NVivo 11 software and thematically analyzed. The majority of participants identified HIV as a Western illness requiring biomedical treatment with an origin largely attributed to biological mechanisms. A traditional form of HIV only cured using traditional treatments was also denoted. Unlike for HIV, the majority of respondents felt that there was no biological or behavioral cause for mental illness but rather the illness was conceptualized supernaturally thus likely impacting patient care pathways. Further research to study HIV and mental health perceptions among a larger sample in different regions of sub-Saharan Africa is warranted.